Syagrus romanzoffiana - Jorge, Neuza [UNESP]; da Silva, Ana Carolina; Veronezi, Carolina Médici [UNESP] (Springer Nature, 2021)
Palm trees belong to the family Arecaceae and are often considered an ecologically relevant species, since they present low fructification synchrony and represent, in times of food scarcity, an important source of resources for the fauna. This family is formed by several genera and species, including Syagrus romanzoffiana (Cham.) Glassman., which is a palm tree found in several countries, but endemic in South America. In Brazil, it is spread from North to South, through almost all vegetable formations, including the Cerrado. Although it is a fruit tree with great agricultural potential, its use in food is more restricted to consumption of the fruits in natura. The Syagrus romanzoffiana fruit has a very fibrous and orange colored pulp, due to the presence of carotenoids. It can be used to treat diseases of the digestive and renal systems. The kernel is rich in oil predominantly composed of saturated fatty acids and, consequently, of high oxidative stability. Thus, the purpose of this chapter is to collect information available on Syagrus romanzoffiana, covering various aspects of the plant, mainly the fruit pulp and kernel and their possible nutritional, biological, and pharmacological applications, in order to disseminate the importance of this species.